From Rationality to Reality: A Systematic Synthesis of Behavioral Biases and Irrationality in Global Real Estate Markets - Muhammad Sahlan; Eko Susanto (Journal of Consumer Studies and Applied Marketing, 2025)
The traditional paradigm of real estate finance is currently undergoing a fundamental transition from neoclassical "Rationality" to a more nuanced "Behavioral Reality." This study provides a systematic literature review (SLR) of the behavioral biases influencing global property markets, synthesizing evidence from 97 peer-reviewed documents indexed in Scopus and Web of Science over 26 years (1999–2025). Following the PRISMA 2020 protocol, the review addresses four critical research questions regarding the evolution, taxonomy, geographical distribution, and market impact of behavioral heuristics. The findings reveal a significant surge in publication density between 2020 and 2025, driven by global economic uncertainty and the digitalization of property markets. A comprehensive taxonomy identifies herding behavior as the most dominant bias, functioning as a psychological bridge between individual cognitive errors (e.g., anchoring) and collective social sentiment. Methodologically, the landscape is shifting from macro-econometric modeling toward experimental designs, particularly in measuring "investor mood." Geographically, a stark divergence is observed: emerging markets (e.g., China, Turkey, and Poland) exhibit significantly higher bias intensity and "intentional herding" compared to developed markets, primarily due to lower institutional transparency. Ultimately, the persistent decoupling of house prices from fundamental values during bubble formations confirms the limitations of the Efficient Market Hypothesis (EMH). The study advocates for the Adaptive Market Hypothesis (AMH) as a superior framework for understanding the "predictable irrationality" of market participants. These insights offer practical implications for investors, practitioners, and policymakers in developing behaviorally informed "early warning systems" to mitigate systemic volatility in the global real estate ecosystem.